PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR PKN MATERI NILAI-NILAI PANCASILA DALAM PRAKTIK PENYELENGGARAAN PEMERINTAH NEGARA PADA SISWA KLEAS X SMAN 5 KOTA BANDA ACEH - Musdiani; Muslia (Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is titled “Application of Model learning Based Learning to improve learning performance of PKN value material of Pancasila in the practice of State Government implementation in grade X students SMAN 5 Banda Aceh”. The problem in this research is the implementation of the students ' learning outcomes on the value of Pancasila material in the practice of government administration in the students of class X SAMN 5 Banda Aceh? This research aims to know the application of the problem based learning model to improve learning performance of PKN material value Pancasila in the practice of government administration in class X SMAN 5 Banda Aceh. The approach in this study is quantitative, while the type of research is PTK. The population in this study is the students of SMAN 5 Banda Aceh. Meanwhile, the student samples of Kleas X IPA 5 are 29 students using conventional learning models. For data collection This research uses pretes and postes. Data is analyzed by using the test-t formula. Data analysis results show that the problem based learning model can improve the learning performance of grade X students of SMAN 5 City Banda Aceh. This suggests that conventional learning models can improve the learning performance of the grade X students of SMAN 5 in Banda Aceh. Abstrak Penelitian ini berjudul